Ciężar ojcostwa w Księdze Ozeasza - Szmajdziński, Mariusz (Verbum Vitae, 2015)
In the Book of Hosea a noun "'ab" does not appły to the prophet or Yahweh, but an idea of their fatherhood occurs in the prophecy. The prophet was called to be a husband of the woman of whoredom and a father of the children of whoredom. Hosea accepted this calling and consequently remained in love with them. In this way he became an image of God's love for His people. In the marital and parental story of Hosea, Yahweh reveals His torn heart. It shows that He not only loves Israel, but also how does it. In the face of the continuous infidelity of the Chosen People, God's love must be stronger than human sin. It was shown in the image of patemal and motherly love, it signifies complete love which was expressed in a human way in the Book of Hosea. Yahweh always forgives, loves and gives new life. In spite of the fact that Israel is really "the son of whoredom" who rejects love and knowledge of God as his Father and Saviour, he still remains in the bonds of God's incomprehensible love and is called "the son of God".